Evaluation Analysis of the Implementation of the Principle of Legality in Indonesian State Administrative Law: A Case Study of the Revocation of Mining Business Permits PT Beri Mineral Utama in Aceh - Jum Anggriani; Muhammad Chaerul Ichsan (Inovasi Pratama Internasional. Ltd, 2026)
This study analyzes the application of the legality principle in the revocation of PT Beri Mineral Utama's Mining Business License in Aceh using a normative juridical approach. The research focuses on evaluating three dimensions of the legality principle: authority, procedure, and substance. Analysis of legal documents and interviews with experts revealed significant non-compliance with the legality principle, with the Governor of Aceh committing ultra vires acts, ignoring the legally mandated written warning procedure, and basing the revocation on outdated grounds. The court ruling overturning the permit revocation underscores the importance of a strict interpretation of the legality principle in burdensome administrative actions. This non-compliance not only has legal implications but also has significant socio-economic consequences, including mass layoffs and reduced regional revenues. This study contributes to the development of an analytical framework for comprehensively evaluating the application of the legality principle and recommends a more adaptive and equitable reconstruction of its implementation. This case underscores the urgency of strengthening institutional capacity in mining management and the importance of balancing legal certainty with considerations of community welfare.